Hybrid or modified optimization algorithms for dam reservoir water operation: A review - Nurhikmah F.; Hossain M.S.; Zawawi M.H. (American Institute of Physics Inc., 2023)
Determination of optimum policy for scarce water resources plays an important role in the sustainable development of any region. Generally, optimal operation of reservoir is one of the challenging problems for water resources systems. In other words, optimal operation of reservoir plays an important role for water resources planning and management. The major goal of reservoir operation optimization problem is to decide how much water should be released and how much should be stored for future uses. In the last decades, the computational researchers have been increasingly interested to the natural sciences, and especially biology, as source of modeling paradigms. Many research areas are massively influenced by the behavior of various biological entities and phenomena. It gave birth to most of population-based Metaheuristics such as Evolutionary Algorithms (EAs), Particle Swarm Optimization (PSO), Artificial Bee Colony (ABC) etc. 2018 Author(s).